Manejo y conservación de polen de Tectona grandis y Gmelina arborea - Hine, Ana (2020)
Hine Gómez, A. L. (2020). Manejo y conservación de polen de Tectona grandis y Gmelina arborea. [Tesis de Doctorado]. Universidad Nacional, Costa Rica.